Domino reactions of 2H-azirines with acylketenes from furan-2,3-diones: Competition between the formation of ortho-fused and bridged heterocyclic systems - Khlebnikov, Alexander F.; Novikov, Mikhail S.; Pakalnis, Viktoriia V.; Iakovenko, Roman O.; Yufit, Dmitry S. (Beilstein Journal of Organic Chemistry, 2014)
3-Aryl-2H-azirines react with acylketenes, generated by thermolysis of 5-arylfuran-2,3-diones, to give bridged 5,7-dioxa-1-azabicyclo[4.4.1]undeca-3,8-diene-2,10-diones and/or ortho-fused 6,6a,12,12a-tetrahydrobis[1,3]oxazino[3,2-a:3′,2′-d]pyrazine-4,10-diones. The latter compounds, with a new heterocyclic skeleton, are the result of the coupling of two molecules of azirine and two molecules of acylketene and can be prepared only from 3-aryl-2H-azirines having no electron-withdrawing groups in the aryl substituent. Calculations at the DFT B3LYP/6-31G(d) level for the various routes of bis[1,3]oxazino[3,2-a:3′,2′-d]pyrazine skeleton formation revealed a new domino reaction of 3-aryl-2H-azirines occurring in the presence of furandiones: acid-catalyzed dimerization to dihydropyrazine followed by consecutive cycloaddition of the latter to two molecules of acylketenes.
Keywords: acylketene; azirine; domino reaction; furandione